The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1044/1059-0889(1998/014)
|View full text |Cite
|
Sign up to set email alerts
|

Tympanometric Screening Norms for Adults

Abstract: The purpose of this study was to reexamine the Margolis and Heller (1987) normative tympanometric data (also American Speech-Language-Hearing [ASHA], 1990 interim norms) using a strict control over subject age and gender. Normative values for peak, compensated static acoustic admittance (Peak Ytm), acoustic equivalent volume (Vea), and tympanometric width (TW) were determined for 102 young adults with normal hearing. Relative to the Margolis and Heller normative values, significant differences were found for V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 5 publications
6
82
0
Order By: Relevance
“…However, when Margolis and Heller's (1987) data were compared with Wiley et al's (1996) data obtained from adults aged 48 to 92 years, the participants in Margolis and Heller's (1987) study had significantly greater Ytm, smaller ear canal volume (Vea) and larger tympanometric Wideband Energy Absorbance in Adults width (TW). In another study, Roup et al (1998) found that their participants, aged 20 to 30 years, had significantly higher Vea and smaller TW than the participants in Margolis and Heller's (1987) study. Nevertheless, these differences in 226-Hz tympanometric parameters across age groups between studies do not provide sufficient evidence of an age effect on the outer and middle ear because of the differences in subject samples, equipment and experimental design.…”
Section: Introductionmentioning
confidence: 99%
“…However, when Margolis and Heller's (1987) data were compared with Wiley et al's (1996) data obtained from adults aged 48 to 92 years, the participants in Margolis and Heller's (1987) study had significantly greater Ytm, smaller ear canal volume (Vea) and larger tympanometric Wideband Energy Absorbance in Adults width (TW). In another study, Roup et al (1998) found that their participants, aged 20 to 30 years, had significantly higher Vea and smaller TW than the participants in Margolis and Heller's (1987) study. Nevertheless, these differences in 226-Hz tympanometric parameters across age groups between studies do not provide sufficient evidence of an age effect on the outer and middle ear because of the differences in subject samples, equipment and experimental design.…”
Section: Introductionmentioning
confidence: 99%
“…Tympanometry was performed in test ears (Interacoustics Audio Traveler AA220, Interacoustics, Assens, Denmark). All subjects had normal equivalent ear canal volume, peak pressure, and compliance (Roup et al, 1998). Subjects were chosen to form pairs based on similarity in hearing thresholds near the SOAE frequency of the SOAEþ subject.…”
Section: A Subjectsmentioning
confidence: 99%
“…The aim of the present study was to develop the open-set Turkish Monosyllabic Word Recognition Test (TMWRT) for adults. , and they had pure-tone air conduction thresholds of less than 10 dB HL at all octave frequencies from 250 to 8000 Hz and static acoustic admittance between 0.3 and 1.4 mmhos, with peak pressure between -100 and +50 daPa [24,25] . For each subject, the ear with the better pure-tone average thresholds at 500 Hz, 1000 Hz, and 2000 Hz was selected as the test ear.…”
Section: Introductionmentioning
confidence: 99%